Psychogenic Nonepileptic Seizures in Women - Dworetzky, Barbara A.; Baslet, Gaston (Seminars in Neurology, 2017)
Psychogenic nonepileptic seizures (PNES) are the most common type of functional neurological symptom disorders and are frequently diagnosed in tertiary care epilepsy monitoring units. These are associated with significant decline in social functioning and quality of life. The majority of patients with PNES are women, outnumbering men by a ratio of 3:1. Female sex preponderance occurs after puberty and usually before the age of 55 years. Many of the psychiatric risk factors in PNES (depression, anxiety, history of traumatic experiences, other somatic symptom disorders) are more common in women and may partially account for the difference in sex prevalence. Neurobiological and neurohumoral mechanisms may also play a role, but our understanding is limited at this point. In this review, we present information on epidemiology and risk factors, neurobiological and psychological mechanisms, clinical approach to diagnosis, evidence-based treatment, and long-term outcomes. We highlight findings related to differences between women and men in PNES. Most of these data are not decisive and require further corroboration. While the disorder may be more frequently suspected in women, all patients with suspected PNES deserve an objective and thorough investigation of their symptoms. Early and accurate identification of this disorder should be a priority, especially as evidence-based treatments, which may lead to improved outcomes, are increasingly available.
Keywords: psychogenic nonepileptic seizures; functional neurological disorder; female; women; risk factors; diagnosis; evidence-based treatment; sex differences